Microclonal Propagation of Promising Grapevine Genotypes - Sa’dullayeva Umida Valijon qizi; Eshbekova Guljaxon G‘ofur qizi (American Journal of Biodiversity, 2026)
Microclonal propagation of promising grapevine genotypes is considered one of the important directions of modern biotechnology. This method enables the rapid production of genetically stable, disease-free, and high-quality planting materials within a short period of time. During the in vitro propagation of plant tissues, the composition of nutrient media, the concentration of phytohormones, and sterilization stages directly affect regeneration efficiency. Research results have shown that the microclonal propagation method is highly effective for the rapid multiplication of high-yielding grapevine cultivars. This article presents an analysis of scientific studies conducted on the microclonal propagation of promising grapevine genotypes and highlights their practical significance.